Na svoji poti - Horreau, Cécile (Slovenia, 2010)
Martina is 17 years-old. She is ambitious and successful. She goes to high school and imagines for her future an independent woman’s life “without being married too early”. Her wish: to become a filmmaker. Nothing weird for a teenager. But Martina is an example of a woman’s determination. She is Roma and wants to make things evolve in her community and outside of it; she wants to change it. Her project: to shoot a movie about her culture. Her plan: to go to Serbia, France and Hungary to meet and explore Roma traditions. Her main actors: the discrete but mainstays of the Roma society, the women.
Donation from OSI-Budapest Arts and Culture Program.
Keywords: Documentary films